Employee Engagement and Organisational Performance in A Public Sector Organisation in Zimbabwe - Peter Sibanda; Taruona Muchena,; Farai Ncube (Asian Economic and Social Society, 2023)
The research analyses employee engagement as a precursor to unlocking organisational performance in a public sector organisation in Zimbabwe. The organisation (herein referred to as Zim-PSO), which has been plagued by operational and people challenges, is essentially locked in underperformance, which, it is argued, could improve as employee engagement levels also improved. A sample of 50 subjects participated in the research. Data were gathered using a combination of unstructured interviews, self-administered questionnaires and a content analysis of a range of secondary data sources in the organisation. A thematic analysis method was used to interpret and analyse the findings. The central argument in the research is that employee engagement is very critical in determining employee, and organisational performance. Findings reveal low levels of employee engagement that consequently result in a below-standard performance amongst the majority of employees. Attempts have been made to improve the work climate and motivation of employees, but the interventions are still insufficient. Whilst the organisation has suffered from a number of perennial problems, much way beyond what engagement can fix, this does not necessarily dwarf the capacity of engagement to stimulate positive employee behaviours that affect productivity and labour efficiency.